High dietary protein restores overreaching induced impairments in leukocyte trafficking and reduces the incidence of upper respiratory tract infection in elite cyclists ? - Witard, O. C.; Turner, J. E.; Jackman, S. R.; Kies, A. K.; Jeukendrup, A. E.; Bosch, J. A.; Tipton, K. D. (Brain, Behavior, and Immunity, 2013)
The present study examined whether a high protein diet prevents the impaired leukocyte redistribution in response to acute exercise caused by a large volume of high-intensity exercise training. Eight cyclists (VO2max: 64.2 ± 6.5 mL kg-1 min-1) undertook two separate weeks of high-intensity training while consuming either a high protein diet (3 g kg-1 protein BM-1 day-1) or an energy and carbohydrate-matched control diet (1.5 g kg-1 protein BM-1 day-1). High-intensity training weeks were preceded by a week of normal-intensity training under the control diet. Leukocyte and lymphocyte sub-population responses to acute exercise were determined at the end of each training week. Self-reported symptoms of upper-respiratory tract infections (URTI) were monitored daily by questionnaire. Undertaking high-intensity training with a high protein diet restored leukocyte kinetics to similar levels observed during normal-intensity training: CD8+ TL mobilization (normal-intensity: 29,319 ± 13,130 cells/µL × ~165 min vs. high-intensity with protein: 26,031 ± 17,474 cells/µL × ~165 min, P > 0.05), CD8+ TL egress (normal-intensity: 624 ± 264 cells/µL vs. high-intensity with protein: 597 ± 478 cells/µL, P > 0.05). This pattern was driven by effector-memory populations mobilizing (normal-intensity: 6,145 ± 6,227 cells/µL × ~165 min vs. high-intensity with protein: 6,783 ± 8,203 cells/µL × ~165 min, P > 0.05) and extravastating from blood (normal-intensity: 147 ± 129 cells/µL vs. high-intensity with protein: 165 ± 192 cells/µL, P > 0.05). High-intensity training while consuming a high protein diet was associated with fewer symptoms of URTI compared to performing high-intensity training with a normal diet (P < 0.05). To conclude, a high protein diet might reduce the incidence of URTI in athletes potentially mediated by preventing training-induced impairments in immune-surveillance.